Evaluation of the Mechanical Properties of Concrete Mixed with Water-Soluble Polymer - Dele Roger Simeon; Aliu Adebayo Soyingbe; Rabiu Aminu (ITEGAM-JETIA)
Polyvinyl alcohol (PVA) is a water-soluble polymer whose impact on concrete properties requires further investigation. Thus, this study established the appropriate dose and applicability of PVA to produce the foremost improvement in the mechanical characteristics of concrete. The study produced 40 concrete cubes and 12 cylinders of concrete specimens at 0%, 0.5%, 1%, 1.5%, and 2% doses of PVA. A number of tests were carried out on the specimens to ascertain their performances. The results showed that a 0.5% addition of PVA to the concrete mixture yields an optimal compressive strength of 24.98N/mm2 after 28 days, while the tensile strength increased as the percentage of PVA increased. Besides, the bond strength of the PVA-modified concrete decreased as the proportion of PVA in the concrete mixture increased. The study concludes that a 0.5% addition of PVA to concrete is the ideal dose for enhanced compressive strength. Also, the study concludes that, while the tensile strength of concrete increases with increasing PVA doses, the bond strength of concrete and rebars decreases as the percentage of PVA increases. This implies that PVA is unsuitable for reinforced concrete structural works. The study therefore recommends that PVA should be applied for non-structural reinforced concrete works.